ENAXON SIDDIQOVA SHE’RIYATIDA QO‘LLANGAN ANTONIMLARNING USLUBIY VAZIFALARI (Intent Research Scientific Journal, 2023)
In order to ensure poetic individuality in the language of the artistic work, the creators use all language units effectively. In particular, antonyms are considered the main tool in fully revealing the purpose of writers and poets. This article examines the features of the use of antonyms in Enakhon Siddikova's poetry.